TAKSASI PRODUKSI MATA TUNAS SEBAGAI BENIH TEBU (SACHARRUM OFFICINARUM L.) DENGAN PENDEKATAN ANALISA REGRESI - Khuluq, Ahmad Dhiaul; Hamida, Ruly (Informatika Pertanian, 2016)
One of the problems encountered in the development of sugarcane (Sacharrum officinarum L.) includes the availability of sugarcane seed both in quality and quantity. Evaluation of bud sett planting method in seed production was required in order to achieve the expected results. The study was conducted at the experiment station Muktiharjo, Central Java in 2012 using PSJT 941 varieties. Treatments applied were the different number of buds on bud sett which were at 3 levels, 1 bud, 2 buds or 3 buds. Research was arranged in a randomized complete block design (RCBD) with 5 replications. Observations were conducted on germination, tillering, plant height, number of stems, number of suckers and number of buds. The data obtained were analyzed with ANOVA and further tested using the Duncan test. Production assessment modeling approach was performed by a regression analysis. Calculation of stem number on 2 buds showed the highest with 9.6 stems/m, 9.2 buds/stem and with the sucker numbers lowest at 0.38 suckers/m. The highest production buds was obtained at planting 2 buds with 847,848.06 buds/ha which can be used as 8.83 ha for the milled sugarcane plantation. Assessment of bud production per hectare could use equation Y = 159655,48.e0,171.X with the independent variable of stem numbers per meter with a correlation coefficient of 0,9007 and a standard error of 1,0699.